Intra-party democracy at the grass root level in Nigeria : candidate selection in the Peoples' Democratic Party, Kaduna North, 2007-2011 - Yusuf, Yahaya Musa (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2014)
Political parties provide the platforms on which candidates contest elections in a multiparty democracy. Many methods exist for the selection process by political parties. In some places, it is regulated by legal frame work and in others; there is a greater level of flexibility. Many factors affect this process particularly in emerging democracies that grapple with primordial political culture. This study attempts to study how the Peoples Democratic Party selects its chairmanship candidates at the grass root level in Kaduna North Nigeria and assess the factors that affect the selection process. The study is a quantitative one and uses a questionnaire to collect data from the delegates who participated in the selection. A sample size of 180 is used out of the 300 research population. A 5-point Likert scale is used in the questionnaire. A statistical tool is used to analyze the data collected. The findings of this research show that the party uses an indirect method guided by a legal framework. There is also a positive correlation between internal and external factors relating to delegates in the candidate selection process. But internal factors have a greater influence than the external factors. Therefore, it shows that despite observance of rules, internal party politics is full of problems which may lead to party members' defection, factionalism, etc.